Application of surfactant containing perchlorate in battery electrolyte
By adding perchlorate-containing surfactant to the lithium sulfur battery electrolyte, the problem of battery performance degradation caused by lithium dendrites is solved, and the battery cycle stability and Coulomb efficiency are improved.
Patent Information
- Application Number
- CN202411903371.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-11
AI Technical Summary
The growth of lithium dendrites in lithium sulfur batteries leads to attenuation of battery capacity, reduced Coulomb efficiency and shortened cycle life, and the low conductivity of sulfur inhibits electrochemical reactions.
The surfactant containing perchlorate was added to the battery electrolyte, and a SEI film rich in LiCl was formed by ClO4-decomposition, which inhibited the growth of lithium dendrites and further inhibited the formation of lithium dendrites through the enrichment and repulsion mechanism of cations.
Effectively inhibit the growth of lithium dendrites, improve the cycle stability performance and Coulomb efficiency of the battery, improve the interface status of the battery, and extend the cycle life of the battery.
Smart Images

Figure CN119812467A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrolytes, and in particular relates to the application of a surfactant containing perchlorate in battery electrolytes. Background Art
[0002] The utilization and development of new and renewable energy sources have become a hot topic of research in countries around the world. The improvement of the performance of energy storage devices can effectively promote the application of new energy sources. Among the various energy storage devices, electrochemical energy storage batteries have become one of the important research directions in countries around the world due to their high energy density, good energy conversion efficiency, low pollution, and convenient combination and mobility.
[0003] Among various electrochemical energy storage batteries, lithium metal anode has high capacity (3820mA·h·g -1 ), as graphite (theoretical capacity is 372 mA·h·g -1 ) has been widely studied as an alternative material for lithium-ion battery anodes. The energy density of a battery with a lithium metal anode and a sulfur cathode, a ternary cathode, can reach 700Wh / kg, which has a very bright application prospect. However, lithium polysulfide (LiPS) in lithium-sulfur batteries is 2 S n , n>2) Dissolution and shuttling in the electrolyte will cause the surface of the sulfur positive electrode to be covered with a layer of short-chain lithium sulfide with low ionic conductivity, causing passivation of the sulfur positive electrode surface, loss of active materials, and battery capacity decay; in addition, due to the low conductivity of sulfur, the electrochemical reaction of the battery will be inhibited under lean electrolyte conditions; in the negative electrode, the growth of lithium dendrites will lead to pulverization of the lithium metal electrode and the generation of dead lithium, causing a series of problems such as reduced battery coulombic efficiency and shortened cycle life; the growth of lithium dendrites will also pierce the diaphragm, causing battery short circuit, and even combustion and explosion, which seriously hinders the practical application of lithium-containing batteries such as lithium-sulfur batteries.
[0004] Therefore, how to provide a lithium-containing battery that inhibits the growth of lithium dendrites is a technical problem that technical personnel in this field urgently need to solve. Summary of the invention
[0005] In order to solve the above technical problems, the present invention proposes the use of a surfactant containing perchlorate in a battery electrolyte.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A use of a perchlorate-containing surfactant in a battery electrolyte, wherein the structure of the perchlorate-containing surfactant is shown in Formula I:
[0008]
[0009] Wherein, R1, R2, R3, and R4 are each independently selected from hydrocarbons or halogenated hydrocarbons containing at least one carbon atom.
[0010] Preferably, the hydrocarbon or halogenated hydrocarbon has 1-16 carbon atoms.
[0011] The halogen element includes at least one of F, Cl, Br and I.
[0012] Preferably, the formula I comprises at least one of the compounds shown in the following structures:
[0013]
[0014]
[0015] An additive for battery electrolyte comprises the above-mentioned surfactant containing perchlorate.
[0016] Beneficial effect: ClO in the electrolyte additive provided by the present invention 4 - It can decompose into LiCl-rich SEI film on the surface of lithium negative electrode during charge and discharge, inhibiting the growth of lithium dendrites. In addition, under the action of electric field force and surface tension, part of the additive cation will be enriched on the surface of lithium dendrite seed, and under the action of battery force, it will repel Li + It is enriched on the surface of lithium dendrite seeds, thereby further inhibiting the formation of lithium dendrites. 1 , R 2 , R 3 , R 4 Each independently selected from hydrocarbons or halogenated hydrocarbons containing at least one carbon atom, since the additive (R 1 R 2 R 3 R 4 )N + Can be used with S n - (1≤n≤8) strong interaction, thereby increasing S n - Dissolves at the electrode / electrolyte interface, increasing the S content in the positive electrode material n - The electrochemical reaction activity enables lithium-sulfur batteries to have a higher battery capacity even under poor electrolyte conditions. 1 R 2 R 3 R 4 )N + It can also guide Li 2 S n Three-dimensional deposition can effectively inhibit the Li 2 S nThe battery passivation problem caused by two-dimensional deposition; therefore, the electrolyte containing this additive can effectively inhibit the Li 2 S n The shuttling effect and growth of lithium dendrites can be reduced, thereby improving the cycle stability of the battery.
[0017] Preferably, the battery electrolyte additive further comprises nitrate;
[0018] The nitrates include nitrobenzene, LiNO 3 、NaNO 3 At least one of .
[0019] Beneficial effects: The above-mentioned LiNO 3 or NaNO 3 The shuttling effect of polysulfides can be further suppressed, so that adding nitrates on the basis of adding the compound shown in the general structural formula I can further improve the capacity utilization and cycle efficiency of the lithium-sulfur battery.
[0020] The invention discloses an application of an additive for battery electrolyte in the electrolyte.
[0021] An electrolyte comprising the above-mentioned battery electrolyte additive, a solvent and an electrolyte;
[0022] Preferably, the content of the battery electrolyte additive in the electrolyte is ≥ 0.1 wt%.
[0023] Preferably, the content of the battery electrolyte additive in the electrolyte is 0.1wt%-30wt%, more preferably 0.5wt%-25wt%, 0.5wt%-15wt%, 0.5wt%-10wt%, 0.5wt%-8wt%, 0.5wt%-5wt%, 1wt%-8wt%, 1wt%-5wt%, 1.5wt%-8wt%, 2wt%-8wt%, 2wt%-7wt%, 2wt%-6wt% or 2wt%-5wt%.
[0024] More preferably, the content of the battery electrolyte additive in the electrolyte is 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt%, 21wt%, 22wt%, 23wt%, 24wt%, 25wt%, 26wt%, 27wt%, 28wt%, 29wt% or 30wt%.
[0025] Beneficial effect: When the additive can be quickly dissolved, increasing the content of the additive in the electrolyte can increase the stable cycle times of the battery, but when the content of the additive in the electrolyte is too high, it will affect the dissolution of the additive in the electrolyte, which is not conducive to improving the stable cycle times of the battery. It can be understood that the content of the additive in the electrolyte can be adjusted according to the ability of the additive to be quickly dissolved in the electrolyte.
[0026] Preferably, the solvent includes at least one of a fluorinated solvent, ethylene glycol dimethyl ether, dimethyl carbonate, 1,3-dioxolane, vinylene carbonate, propylene carbonate, ethylene carbonate, diethyl carbonate, ethyl methyl carbonate, propylene sulfite and methyl propionate.
[0027] More preferably, the fluorinated solvent includes but is not limited to at least one of fluoroethylene carbonate, 3,3,3-trifluoroethyl methyl carbonate, 1,1,2,2-tetrafluoroethyl-2',2',2'-trifluoroethyl ether, and tris(2,2,2-trifluoroethyl)phosphite;
[0028] In addition, the solvent in the present invention can be realized by using an ester electrolyte solvent or an ether electrolyte solvent.
[0029] Preferably, the electrolyte comprises LiPF 6 (Lithium hexafluorophosphate), LiBF 4 (lithium tetrafluoroborate), LiBOB (lithium bis(oxalatoborate), LiClO 4 (lithium perchlorate), LiCF 3 SO 3 (lithium trifluoromethanesulfonate), LiODFB (lithium difluorooxalatoborate), LiN (SO 2 CF 3 ) 2 (Lithium bis(trifluoromethylsulfonyl)imide), LiN(SO 2 F) 2 (lithium bis(monofluoromethylsulfonyl)imide), LiTFSI (lithium bis(trifluoromethanesulfonyl)imide), LiFSI (lithium bis(fluorosulfonyl)imide), LiHFDF (1,1,2,2,3,3-hexafluoropropane-1,3-disulfonic acid imide lithium), NaTFSI (sodium bis(trifluoromethylsulfonyl)imide), KTFSI (potassium bis(trifluoromethylsulfonyl)imide) and at least one of a cyclic imide salt.
[0030] Among them, LiN(SO 2 CF 3 ) 2 It can also be written as LiN(CF 3 SO 2 )2 , that is, lithium bis(trifluoromethylsulfonyl)imide. Specific cyclic imide salts include, but are not limited to, at least one of 1,1,2,2,3,3-hexafluoropropane-1,3-disulfonic acid imide lithium, 1,1,2,2-tetrafluoroethane-1,3-disulfonic acid imide lithium, 1,1,2,2,3,3,4,4-octafluorobutane-1,3-disulfonic acid imide lithium, and the like.
[0031] Beneficial effect: The electrolyte provided by the present invention contains the above-mentioned additives, which can inhibit the growth of lithium dendrites and improve the cycle stability and coulombic efficiency of the battery. At the same time, the lithium salt and nitrate in the electrolyte will decompose on the surface of the lithium negative electrode to form LiF, Li 2 O,Li 3 N inorganic compounds, the anion part of the additive, can also be decomposed into LiCl, and the above-mentioned LiF, Li 2 O,Li 3 N constitutes the inorganic layer in the SEI film of the lithium negative electrode. The inorganic layer has high ion conductivity and can effectively inhibit the growth of lithium dendrites. The cation part will be adsorbed on the surface of the SEI film. When the SEI film is broken, the fresh Li metal surface is exposed. The cation part will be adsorbed on the exposed Li metal surface under the action of electric field force and surface tension, inhibiting the growth of Li + It deposits on the exposed lithium metal surface, thereby inhibiting the growth of lithium dendrites. The cations adsorbed on the lithium metal surface will also decompose to form a new SEI film, which can self-repair the damaged SEI film. Under the synergistic effect of additives and lithium salt anions, the growth of lithium dendrites can be effectively inhibited.
[0032] An application of an electrolyte in a secondary battery.
[0033] A secondary battery comprises the above electrolyte.
[0034] Preferably, the secondary battery further comprises a positive electrode material, a negative electrode material and a separator, wherein the separator is located between the positive electrode material and the negative electrode material of the lithium-containing battery;
[0035] The separator is mainly used to separate the positive and negative electrodes of the battery to prevent the two electrodes from contacting and short-circuiting; in addition, it can also allow electrolyte ions to pass through.
[0036] The positive electrode material includes one or more of copper, sulfur, sulfur-containing composite materials, lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, and ternary materials;
[0037] Preferably, the ternary material comprises a polymer of nickel, cobalt and manganese.
[0038] Preferably, the positive electrode material, the negative electrode material and the electrolyte include lithium element.
[0039] Since the electrode of the secondary battery contains lithium or the electrolyte contains lithium, when the additive is applied to the electrolyte of the secondary battery containing lithium, due to (R 1 R 2 R 3 R 4 )N + Can be used with S n - (1≤n≤8) strong interaction, thereby increasing S n - Dissolves at the electrode / electrolyte interface, increasing the S content in the positive electrode material n - The electrochemical reaction activity enables lithium-sulfur batteries to have a higher battery capacity even under poor electrolyte conditions.
[0040] Compared with the prior art, the present invention has the following advantages and technical effects:
[0041] The ClO in the electrolyte additive provided by the present invention 4 - It can decompose into a LiCl-rich SEI film on the surface of the lithium negative electrode during the charge and discharge process, inhibiting the growth of lithium dendrites. The electrolyte containing the additive can effectively improve the interface condition of the secondary battery, inhibit the growth of lithium dendrites and inhibit Li 2 S n The shuttle effect of the battery can greatly improve the cycle performance of the battery. In addition, the electrolyte additive provided by the present invention is easy to obtain and is conducive to industrial promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0043] Figure 1 The graph is a test result of the coulombic efficiency of the Li-Cu battery obtained in Example 1 of the present invention and Comparative Example 1 during the charge and discharge cycle;
[0044] Figure 2 The voltage curve test result diagram of the Li-Li symmetrical battery obtained in Example 2 of the present invention and Comparative Example 3 during the charge and discharge cycle;
[0045] Figure 3 The electrochemical test results of the Li-S batteries obtained in Example 3 of the present invention and Comparative Example 3 are shown;
[0046] Figure 4 This is a SEM image of the sulfur positive electrode of the Li-S battery obtained in Example 3 of the present invention after 50 charge and discharge cycles;
[0047] Figure 5 This is a SEM image of the sulfur positive electrode of the Li-S battery obtained in Comparative Example 3 of the present invention after 50 charge and discharge cycles;
[0048] Figure 6 This is a SEM image of the lithium electrode of the Li-Li symmetric battery obtained in Example 2 of the present invention after 50 charge and discharge cycles;
[0049] Figure 7 This is a SEM image of the lithium electrode of the Li-Li symmetric battery obtained in Comparative Example 2 of the present invention after 50 charge and discharge cycles. DETAILED DESCRIPTION
[0050] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0051] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0052] Unless otherwise specified, the raw materials in the examples of the present invention were purchased from commercial sources.
[0053] Among them, DOL is 1,3-dioxolane, DME is ethylene glycol dimethyl ether, EC is ethylene carbonate, DMC is dimethyl carbonate, FEC is fluoroethylene carbonate, and TTFP is tris(2,2,2-trifluoroethyl)phosphite.
[0054] Unless otherwise specified, the room temperature or normal temperature in the embodiments of the present invention refers to 25±3°C.
[0055] The stable cycle number in the embodiment of the present invention refers to the cycle number at which the coulombic efficiency of the battery is ≥ 98% after cycling.
[0056] Example 1
[0057] A method for preparing an electrolyte, comprising the following raw materials:
[0058] LiTFSI (lithium bis(trifluoromethanesulfonyl imide)) was dissolved in a mixed solvent (DOL and DME were mixed in a volume ratio of 1:1) to obtain a solution with a LiTFSI concentration of 1 M, and then 3 wt% (CH 3 ) 4 NClO 4 (tetramethylammonium perchlorate, compound 1) and 4 wt% LiNO 3The electrolyte is obtained by mixing and dissolving.
[0059] A Cu-Li battery comprises the above electrolyte, a positive electrode and a negative electrode, wherein the positive electrode material is Cu and the negative electrode material is Li, and the Cu-Li battery is obtained after assembly.
[0060] Performance test: The prepared Cu-Li battery was 2 At a current density of , the deposition / stripping was performed for 1 h each to obtain the battery coulombic efficiency and cycle life.
[0061] Example 2
[0062] A Li-Li battery comprises the electrolyte obtained in Example 1, a positive electrode and a negative electrode, wherein the positive electrode material is Li, and the negative electrode material is Li, and the Li-Li battery is obtained after assembly.
[0063] Performance test: The prepared Li-Li symmetric battery was charged at 1 mA / cm 2 At a current density of , the deposition / stripping was performed for 1 h each to obtain the battery coulombic efficiency and cycle life.
[0064] Example 3
[0065] A lithium-sulfur battery comprises the electrolyte obtained in Example 1, a positive electrode and a negative electrode, wherein the positive electrode material is a S / C composite, and the negative electrode material is Li, and a S / C-Li battery is obtained after assembly.
[0066] The preparation method of the S / C complex comprises the following steps:
[0067] The material with a mass ratio of S:C of 3:2 was fully mixed and calcined at 155°C for 12 hours. After the calcination, the obtained product was washed with ethanol and water, and then dried at 200°C to remove the sulfur on the surface of the material, thereby obtaining an S / C composite, which was used as a positive electrode material for a battery.
[0068] Performance test: charge and discharge at a current density of 1C.
[0069] Example 4
[0070] A method for preparing an electrolyte, which is different from Example 1 in that LiTFSI is replaced by LiHFDF of an equal amount, and the remaining process steps and parameters are the same as those of Example 1.
[0071] A Cu-Li battery comprises the above electrolyte, and the remaining process steps and parameters are the same as those in Example 1.
[0072] Performance test: The prepared Cu-Li battery was 2At a current density of , the deposition / stripping was performed for 1 h each to obtain the battery coulombic efficiency and cycle life.
[0073] Example 5
[0074] A method for preparing an electrolyte, which is different from Example 1 in that LiTFSI is replaced by LiODFB of an equal amount, and the remaining process steps and parameters are the same as those of Example 1.
[0075] A Cu-Li battery comprises the above electrolyte, and the remaining process steps and parameters are the same as those in Example 1.
[0076] Performance test: The prepared Cu-Li battery was 2 At a current density of , the deposition / stripping was performed for 1 h each to obtain the battery coulombic efficiency and cycle life.
[0077] Example 6
[0078] A method for preparing an electrolyte comprises the following steps:
[0079] LiODFB was dissolved in a mixed solvent (EC and DME were mixed in a volume ratio of 1:1) to obtain a solution with a LiODFB concentration of 1 M, and then 3.75 wt% of the total mass of the electrolyte (CH 3 ) 4 NClO 4 The electrolyte is obtained by mixing and dissolving.
[0080] A Cu-Li battery comprises the above electrolyte, and the remaining process steps and parameters are the same as those in Example 1.
[0081] Performance test: The prepared Cu-Li battery was 2 At a current density of , the deposition / stripping was performed for 1 h each to obtain the battery coulombic efficiency and cycle life.
[0082] Example 7
[0083] A method for preparing an electrolyte comprises the following steps:
[0084] LiODFB was dissolved in a mixed solvent (EC, DME and FEC were mixed in a volume ratio of 4.5:4.5:1) to obtain a solution with a LiODFB concentration of 1 M, and then 3 wt% of the total mass of the electrolyte (CH 3 ) 4 NClO 4 The electrolyte is obtained by mixing and dissolving.
[0085] A Cu-Li battery comprises the above electrolyte, and the remaining process steps and parameters are the same as those in Example 1.
[0086] Performance test: The prepared Cu-Li battery was 2 At a current density of , the deposition / stripping was performed for 1 h each to obtain the battery coulombic efficiency and cycle life.
[0087] Example 8
[0088] A method for preparing an electrolyte, which is different from that of Example 1 in that (CH 3 ) 4 NClO 4 The addition amount is 1wt% of the total mass of the electrolyte, and the remaining process steps and parameters are the same as those in Example 1.
[0089] A Cu-Li battery comprises the above electrolyte, and the remaining process steps and parameters are the same as those in Example 1.
[0090] Performance test: The prepared Cu-Li battery was 2 At a current density of , the deposition / stripping was performed for 1 h each to obtain the battery coulombic efficiency and cycle life.
[0091] Example 9
[0092] A method for preparing an electrolyte, which is different from that of Example 1 in that (CH 3 ) 4 NClO 4 The addition amount is 2wt% of the total mass of the electrolyte, and the remaining process steps and parameters are the same as those in Example 1.
[0093] A Cu-Li battery comprises the above electrolyte, and the remaining process steps and parameters are the same as those in Example 1.
[0094] Performance test: The prepared Cu-Li battery was 2 At a current density of , the deposition / stripping was performed for 1 h each to obtain the battery coulombic efficiency and cycle life.
[0095] Example 10
[0096] A method for preparing an electrolyte, which is different from that of Example 1 in that (CH 3 ) 4 NClO 4 The addition amount is 4wt% of the total mass of the electrolyte, and the remaining process steps and parameters are the same as those in Example 1.
[0097] A Cu-Li battery comprises the above electrolyte, and the remaining process steps and parameters are the same as those in Example 1.
[0098] Performance test: The prepared Cu-Li battery was 2At a current density of , the deposition / stripping was performed for 1 h each to obtain the battery coulombic efficiency and cycle life.
[0099] Embodiment 11
[0100] A method for preparing an electrolyte, which is different from that of Example 1 in that (CH 3 ) 4 NClO 4 The addition amount is 1wt% of the total mass of the electrolyte, LiNO 3 The addition amount is 3wt% of the total mass of the electrolyte, and the remaining process steps and parameters are the same as those in Example 1.
[0101] A Cu-Li battery comprises the above electrolyte, and the remaining process steps and parameters are the same as those in Example 1.
[0102] Performance test: The prepared Cu-Li battery was 2 At a current density of , the deposition / stripping was performed for 1 h each to obtain the battery coulombic efficiency and cycle life.
[0103] Example 12
[0104] A method for preparing an electrolyte comprises the following steps:
[0105] LiODFB was dissolved in a mixed solvent (EC, DMC and FEC were mixed in a volume ratio of 4.5:4.5:1) to obtain a solution with a LiODFB concentration of 1 M, and then 1 wt% of the total mass of the electrolyte (CH 3 ) 4 NClO 4 The electrolyte is obtained by mixing and dissolving.
[0106] A Cu-Li battery comprises the above electrolyte, and the remaining process steps and parameters are the same as those in Example 1.
[0107] Performance test: The prepared Cu-Li battery was 2 At a current density of , the deposition / stripping was performed for 1 h each to obtain the battery coulombic efficiency and cycle life.
[0108] Example 13
[0109] A method for preparing an electrolyte comprises the following steps:
[0110] LiODFB was dissolved in a mixed solvent (EC, DMC and FEC were mixed in a volume ratio of 4.5:4.5:1) to obtain a solution with a LiODFB concentration of 1 M, and then 2 wt% of the total mass of the electrolyte (CH 3 ) 4 NClO 4The electrolyte is obtained by mixing and dissolving.
[0111] A Cu-Li battery comprises the above electrolyte, and the remaining process steps and parameters are the same as those in Example 1.
[0112] Performance test: The prepared Cu-Li battery was 2 At a current density of , the deposition / stripping was performed for 1 h each to obtain the battery coulombic efficiency and cycle life.
[0113] Embodiment 14
[0114] A method for preparing an electrolyte comprises the following steps:
[0115] LiODFB was dissolved in a mixed solvent (EC, DMC and FEC were mixed in a volume ratio of 4.5:4.5:1) to obtain a solution with a LiODFB concentration of 1 M, and then 3 wt% of the total mass of the electrolyte (CH 3 ) 4 NClO 4 The electrolyte is obtained by mixing and dissolving.
[0116] A Cu-Li battery comprises the above electrolyte, and the remaining process steps and parameters are the same as those in Example 1.
[0117] Performance test: The prepared Cu-Li battery was 2 At a current density of , the deposition / stripping was performed for 1 h each to obtain the battery coulombic efficiency and cycle life.
[0118] Embodiment 15
[0119] A method for preparing an electrolyte comprises the following steps:
[0120] Take LiPF 6 Dissolve in a mixed solvent (EC and DMC mixed in a volume ratio of 1:1) to obtain LiPF 6 A solution with a concentration of 1M was prepared, and then 1wt% of the total mass of the electrolyte (CH 3 ) 4 NClO 4 The electrolyte is obtained by mixing and dissolving.
[0121] A Cu-Li battery comprises the above electrolyte, and the remaining process steps and parameters are the same as those in Example 1.
[0122] Performance test: The prepared Cu-Li battery was 2 At a current density of , the deposition / stripping was performed for 1 h each to obtain the battery coulombic efficiency and cycle life.
[0123] Example 16
[0124] A method for preparing an electrolyte comprises the following steps:
[0125] Take LiPF 6 Dissolve in a mixed solvent (EC and DMC mixed in a volume ratio of 1:1) to obtain LiPF 6 A solution with a concentration of 1M was prepared, and then 2 wt% of the total mass of the electrolyte (CH 3 ) 4 NClO 4 The electrolyte is obtained by mixing and dissolving.
[0126] A Cu-Li battery comprises the above electrolyte, and the remaining process steps and parameters are the same as those in Example 1.
[0127] Performance test: The prepared Cu-Li battery was 2 At a current density of , the deposition / stripping was performed for 1 h each to obtain the battery coulombic efficiency and cycle life.
[0128] Embodiment 17
[0129] A method for preparing an electrolyte comprises the following steps:
[0130] Take LiPF 6 Dissolve in a mixed solvent (EC and DMC mixed in a volume ratio of 1:1) to obtain LiPF 6 A solution with a concentration of 1M was prepared, and then 3 wt% of the total mass of the electrolyte (CH 3 ) 4 NClO 4 The electrolyte is obtained by mixing and dissolving.
[0131] A Cu-Li battery comprises the above electrolyte, and the remaining process steps and parameters are the same as those in Example 1.
[0132] Performance test: The prepared Cu-Li battery was 2 At a current density of , the deposition / stripping was performed for 1 h each to obtain the battery coulombic efficiency and cycle life.
[0133] Embodiment 18
[0134] A method for preparing an electrolyte comprises the following steps:
[0135] Take LiPF 6 Dissolved in a mixed solvent (EC, DMC and TTFP mixed in a volume ratio of 4.5:4.5:1) to obtain LiPF 6 A solution with a concentration of 1M was prepared, and then 2 wt% of the total mass of the electrolyte (CH 3 ) 4NClO 4 The electrolyte is obtained by mixing and dissolving.
[0136] A Cu-Li battery comprises the above electrolyte, and the remaining process steps and parameters are the same as those in Example 1.
[0137] Performance test: The prepared Cu-Li battery was 2 At a current density of , the deposition / stripping was performed for 1 h each to obtain the battery coulombic efficiency and cycle life.
[0138] Embodiment 19
[0139] A method for preparing an electrolyte comprises the following steps:
[0140] Take LiPF 6 Dissolved in a mixed solvent (EC, DMC and TTFP mixed in a volume ratio of 4.5:4.5:1) to obtain LiPF 6 A solution with a concentration of 1M was prepared, and then 1wt% of the total mass of the electrolyte (CH 3 ) 4 NClO 4 The electrolyte is obtained by mixing and dissolving.
[0141] A Cu-Li battery comprises the above electrolyte, and the remaining process steps and parameters are the same as those in Example 1.
[0142] Performance test: The prepared Cu-Li battery was 2 At a current density of , the deposition / stripping was performed for 1 h each to obtain the battery coulombic efficiency and cycle life.
[0143] Embodiment 20
[0144] A method for preparing an electrolyte comprises the following steps:
[0145] Take LiPF 6 Dissolved in a mixed solvent (EC, DMC and TTFP mixed in a volume ratio of 4.5:4.5:1) to obtain LiPF 6 A solution with a concentration of 1M was prepared, and then 3 wt% of the total mass of the electrolyte (CH 3 ) 4 NClO 4 The electrolyte is obtained by mixing and dissolving.
[0146] A Cu-Li battery comprises the above electrolyte, and the remaining process steps and parameters are the same as those in Example 1.
[0147] Performance test: The prepared Cu-Li battery was 2At a current density of , the deposition / stripping was performed for 1 h each to obtain the battery coulombic efficiency and cycle life.
[0148] Embodiment 21
[0149] A method for preparing an electrolyte, which is different from Example 1 in that LiTFSI is replaced by an equal amount of NaTFSI, and the remaining process steps and parameters are the same as those in Example 1.
[0150] A Cu-Na battery comprises the above electrolyte, a positive electrode and a negative electrode, wherein the positive electrode material is Cu and the negative electrode material is Na, and the Cu-Na battery is obtained after assembly.
[0151] Performance test: The prepared Cu-Na battery was subjected to a 2 At a current density of , the deposition / stripping was performed for 1 h each to obtain the battery coulombic efficiency and cycle life.
[0152] Embodiment 22
[0153] A method for preparing an electrolyte, which is different from Example 1 in that LiTFSI is replaced by KTFSI of an equal amount, and the remaining process steps and parameters are the same as those of Example 1.
[0154] A Cu-K battery comprises the above electrolyte, a positive electrode and a negative electrode, wherein the positive electrode material is Cu and the negative electrode material is K, and the Cu-K battery is obtained after assembly.
[0155] Performance test: The prepared Cu-K battery was tested at 1 mA / cm 2 At a current density of , the deposition / stripping was performed for 1 h each to obtain the battery coulombic efficiency and cycle life.
[0156] Embodiment 23
[0157] A method for preparing an electrolyte, which is different from that of Example 1 in that LiNO is not included 3 The remaining process steps and parameters are the same as those in Example 1.
[0158] A Cu-Li battery comprises the above electrolyte, and the remaining process steps and parameters are the same as those in Example 1.
[0159] Performance test: The prepared Cu-Li battery was 2 At a current density of , the deposition / stripping was performed for 1 h each to obtain the battery coulombic efficiency and cycle life.
[0160] Embodiment 24
[0161] A method for preparing an electrolyte, which is different from that in Example 1 in that LiNO 3The mixture was replaced with nitrobenzene of equal mass, and the remaining process steps and parameters were the same as those in Example 1.
[0162] A Cu-Li battery comprises the above electrolyte, and the remaining process steps and parameters are the same as those in Example 1.
[0163] Performance test: The prepared Cu-Li battery was 2 At a current density of , the deposition / stripping was performed for 1 h each to obtain the battery coulombic efficiency and cycle life.
[0164] Examples 25-32
[0165] A method for preparing an electrolyte, which is different from that in Example 1 in that (CH 3 ) 4 NClO 4 Replace with equal quality (C 2 H 5 ) 4 NClO 4 (tetraethylammonium perchlorate, compound 2), compound 3, compound 4, compound 5, compound 6, compound 7, compound 8 and compound 9, and the remaining process steps and parameters are the same as those in Example 1.
[0166] A Cu-Li battery comprises the above electrolyte, and the remaining process steps and parameters are the same as those in Example 1.
[0167] Performance test: The prepared Cu-Li battery was 2 At a current density of , the deposition / stripping was performed for 1 h each to obtain the battery coulombic efficiency and cycle life.
[0168] Comparative Example 1
[0169] A method for preparing an electrolyte, which is different from that of Example 1 in that (CH 3 ) 4 NClO 4 The remaining process steps and parameters are the same as those in Example 1.
[0170] A Cu-Li battery comprises the above electrolyte, and the remaining process steps and parameters are the same as those in Example 1.
[0171] Performance test: The prepared Cu-Li battery was 2 At a current density of , the deposition / stripping was performed for 1 h each to obtain the battery coulombic efficiency and cycle life.
[0172] Comparative Example 2
[0173] A Li-Li battery includes the electrolyte obtained in Comparative Example 1, and the remaining process steps and parameters are the same as those in Example 2.
[0174] Performance test: The prepared Li-Li battery was subjected to 2 At a current density of , the deposition / stripping was performed for 1 h each to obtain the battery coulombic efficiency and cycle life.
[0175] Comparative Example 3
[0176] A lithium-sulfur battery includes the electrolyte obtained in Comparative Example 1, and the remaining process steps and parameters are the same as those in Example 3.
[0177] Performance test: The prepared battery was charged and discharged at a current density of 1C.
[0178] Comparative Example 4
[0179] A method for preparing an electrolyte, which is different from Comparative Example 1 in that LiNO 3 Replace with an equal mass of NaNO 3 The remaining process steps and parameters are the same as those in Example 1.
[0180] A Cu-Na battery comprises the above electrolyte, and the remaining process steps and parameters are the same as those in Example 1.
[0181] Performance test: The prepared Cu-Na battery was subjected to a 2 At a current density of , the deposition / stripping was performed for 1 h each to obtain the battery coulombic efficiency and cycle life.
[0182] Comparative Example 5
[0183] A method for preparing an electrolyte, which is different from Comparative Example 1 in that LiNO 3 Replace with an equal mass of KNO 3 The remaining process steps and parameters are the same as those in Example 1.
[0184] A Cu-K battery comprises the above electrolyte, and the remaining process steps and parameters are the same as those in Example 1.
[0185] Performance test: The prepared Cu-K battery was tested at 1 mA / cm 2 At a current density of , the deposition / stripping was performed for 1 h each to obtain the battery coulombic efficiency and cycle life.
[0186] Comparative Example 6
[0187] A method for preparing an electrolyte comprises the following steps:
[0188] LiODFB was dissolved in a mixed solvent (EC, DMC and FEC were mixed in a volume ratio of 4.5:4.5:1) to prepare a solution with a LiODFB concentration of 1 M, that is, an electrolyte.
[0189] A Cu-Li battery comprises the above electrolyte, and the remaining process steps and parameters are the same as those in Example 1.
[0190] Performance test: The prepared Cu-Li battery was 2 At a current density of , the deposition / stripping was performed for 1 h each to obtain the battery coulombic efficiency and cycle life.
[0191] Comparative Example 7
[0192] A method for preparing an electrolyte comprises the following steps:
[0193] Take LiPF 6 Dissolve in a mixed solvent (EC and DMC mixed in a volume ratio of 1:1) to obtain LiPF 6 A solution with a concentration of 1M is obtained as an electrolyte.
[0194] A Cu-Li battery comprises the above electrolyte, and the remaining process steps and parameters are the same as those in Example 1.
[0195] Performance test: The prepared Cu-Li battery was 2 At a current density of , the deposition / stripping was performed for 1 h each to obtain the battery coulombic efficiency and cycle life.
[0196] Comparative Example 8
[0197] A method for preparing an electrolyte comprises the following steps:
[0198] Take LiPF 6 Dissolved in a mixed solvent (EC, DMC and TTFP mixed in a volume ratio of 4.5:4.5:1) to obtain LiPF 6 A solution with a concentration of 1M is obtained as an electrolyte.
[0199] A Cu-Li battery comprises the above electrolyte, and the remaining process steps and parameters are the same as those in Example 1.
[0200] Performance test: The prepared Cu-Li battery was 2 At a current density of , the deposition / stripping was performed for 1 h each to obtain the battery coulombic efficiency and cycle life.
[0201] Comparative Example 9
[0202] A method for preparing an electrolyte comprises the following steps:
[0203] LiTFSI was dissolved in a mixed solvent (EC, DMC and TTFP were mixed in a volume ratio of 4.5:4.5:1) to prepare a solution with a LiTFSI concentration of 1 M, that is, an electrolyte.
[0204] A Cu-Li battery comprises the above electrolyte, and the remaining process steps and parameters are the same as those in Example 1.
[0205] Performance test: The prepared Cu-Li battery was 2 At a current density of , the deposition / stripping was performed for 1 h each to obtain the battery coulombic efficiency and cycle life.
[0206] Comparative Example 10
[0207] A method for preparing an electrolyte, comprising the following raw materials:
[0208] LiTFSI was dissolved in a mixed solvent (DOL and DME were mixed in a volume ratio of 1:1) to obtain a solution with a LiTFSI concentration of 1 M, and then 4 wt% of the total mass of the electrolyte NaNO was added. 3 The electrolyte is obtained by mixing and dissolving.
[0209] A Cu-Li battery comprises the above electrolyte, a positive electrode and a negative electrode, wherein the positive electrode material is Cu and the negative electrode material is Li, and the Cu-Li battery is obtained after assembly.
[0210] Performance test: The prepared Cu-Li battery was 2 At a current density of , the deposition / stripping was performed for 1 h each to obtain the battery coulombic efficiency and cycle life.
[0211] Technical effects:
[0212] The test results of the positive electrode materials, negative electrode materials and electrolyte components included in the secondary batteries provided in the above Examples 1-25 and Comparative Examples 1-10 and the stable charge and discharge cycle times of the corresponding secondary batteries are shown in Table 1 below.
[0213] Table 1
[0214]
[0215]
[0216]
[0217] It can be seen from Table 1 that, in combination with the results of Examples 1-11 and Comparative Examples 1, 7 and 8, or in combination with the results of Examples 12-20 and Comparative Examples 4-6, when the positive and negative electrode materials and solvents of the secondary battery are the same, adding (CH 3 ) 4 NClO 4 The stable cycle times of the battery can be significantly improved.
[0218] Combining the results of Example 21 and Example 22 with the results of Comparative Example 4 and Comparative Example 5, it can be seen that when the electrode material and the electrolyte do not contain lithium, only when a lithium-containing additive is added to the electrolyte, (CH 3 ) 4 NClO 4 The stable cycle times of the battery can be significantly improved.
[0219] Combining the results of Examples 12-20 and Comparative Examples 6-8, it can be seen that when the electrolyte contains an ester solvent, adding NClO to the electrolyte 4 The stable cycle times of the battery can be significantly improved.
[0220] Combined with the results of Examples 1-25, it can be seen that the solvent composition, electrolyte type or additive (CH 3 ) 4 NClO 4 When the content changes, or when adding (CH 3 ) 4 NClO 4 When other additives are added on the basis of the original material, the stable cycle times of the battery still remain at a high level.
[0221] The number of stable cycles of Examples 12-20 is less than that of Examples 1-11, indicating that the performance of ester electrolyte solvents is worse than that of ether electrolyte solvents.
[0222] The Cu-Li batteries obtained in Example 1 and Comparative Example 1 were heated at 1 mA / cm 2 At a current density of 1.5, the deposition and stripping were performed for 1 h. The coulombic efficiency of the Cu-Li battery during the charge and discharge cycle was tested. Figure 1 As shown, Figure 1 The horizontal axis is the number of cycles, and the vertical axis is the Coulomb efficiency (%). Figure 1 TAPC refers to (CH 3 ) 4 NClO 4 .from Figure 1It can be seen that the coulombic efficiency of the Li-Cu battery without TAPC added to the electrolyte decreased rapidly after 180 charge and discharge cycles, while the coulombic efficiency of the Li-Cu battery with (CH 3 ) 4 NClO 4 After 620 charge and discharge cycles, the coulombic efficiency of the Li-Cu battery remained above 98%, and the cycle performance was greatly improved, indicating that the (CH 3 ) 4 NClO 4 The electrolyte can effectively improve the interface condition of the battery and inhibit the growth of lithium dendrites in the battery.
[0223] The Li-Li symmetrical cells obtained in Example 2 and Comparative Example 2 were heated at 1 mA / cm 2 At a current density of 1.5, the deposition and stripping were performed for 1 h. The voltage curve of the Li-Li symmetric battery during the charge and discharge cycle was tested. Figure 2 As shown, Figure 2 The horizontal axis is time (in hours), and the vertical axis is voltage (in V). Figure 2 It can be seen that the electrolyte in Comparative Example 2 does not contain (CH 3 ) 4 NClO 4 After 400 hours of cycling, the obtained Li-Li symmetric battery rapidly polarized; while in Example 2, when adding (CH 3 ) 4 NClO 4 The electrolyte of the battery has not been polarized after 1500 hours of cycling, which further illustrates that the addition of (CH 3 ) 4 NClO 4 The electrolyte can effectively improve the interface condition of the battery and inhibit the growth of lithium dendrites in the battery.
[0224] The electrolytes of Example 3 and Comparative Example 3 were used to equip Li-S batteries for electrochemical testing, wherein the sulfur loading was ≤2 mg cm -2 , the amount of electrolyte is less than 10μL.mg -1 , that is, the amount of electrolyte added is ≤10μL per mg of sulfur, and the performance of Li-S battery is as follows Figure 3 As shown, from Figure 3 It can be seen that the battery capacity, cycle stability and coulombic efficiency of the Li-S battery using the electrolyte of Example 1 are greatly improved. Figure 4 It can be seen that after the Li-S battery using the electrolyte of Comparative Example 1 was cycled 50 times, Li 2 The deposition of S is flat and flat. Figure 5 As you can see, using (CH3 ) 4 NClO 4 After 50 cycles of Li-S battery with electrolyte, Li 2 The deposition of S is three-dimensional granular, indicating that (R 1 R 2 R 3 R 4 )N + It can also guide Li 2 Sn three-dimensional deposition, inhibiting Li 2 The battery passivation effect caused by S plane deposition can improve the battery cycle stability performance; in addition, (CH 3 ) 4 NClO 4 The cationic part of the additive (i.e. Li + ) are enriched on the surface of lithium dendrite seeds under the action of electric field force and surface tension, and repel Li with the same charge under the action of battery force. + It is enriched on the surface of lithium dendrite seeds, thereby inhibiting the formation of lithium dendrites. 3 ) 4 NClO 4 The electrolyte with additives can effectively improve the Li 2 Sn can enhance the electrochemical reaction activity, inhibit the surface passivation of the sulfur positive electrode and the growth of lithium dendrites, thereby improving the battery capacity and cycle stability of the battery.
[0225] Figure 6 The SEM test results of the Li-Li symmetrical batteries of Example 2 and Comparative Example 2 after 20 charge and discharge cycles are shown in Figure 2. Figure 6 It can be seen that the lithium deposition on the surface of the lithium electrode obtained in Example 2 is dense and uniform, and no obvious dendrites appear, indicating that the use of the electrolyte in Example 1 can effectively inhibit the growth of lithium dendrites. Figure 7 This is the SEM image of the lithium electrode obtained in Comparative Example 2. Figure 7 It can be seen that many fibrous lithium dendrites appear on the surface of the lithium electrode obtained in Comparative Example 2, indicating that LiTFSI cannot inhibit the growth of lithium dendrites.
[0226] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. Application of a surfactant containing perchlorate in a battery electrolyte, characterized in that: The structure of the perchlorate-containing surfactant is shown in Formula I: Wherein, R1, R2, R3, and R4 are each independently selected from hydrocarbons or halogenated hydrocarbons containing at least one carbon atom.
2. A battery electrolyte additive, characterized in that: The invention comprises the perchlorate-containing surfactant according to claim 1.
3. Use of the battery electrolyte additive as claimed in claim 2 in an electrolyte.
4. An electrolyte, characterized in that: The invention comprises the battery electrolyte additive according to claim 2, a solvent and an electrolyte.
5. The electrolyte according to claim 4, characterized in that The content of the battery electrolyte additive in the electrolyte is 0.1-30wt%.
6. The electrolyte according to claim 4, characterized in that The solvent includes one or more of fluorinated solvents, ethylene glycol dimethyl ether, dimethyl carbonate, 1,3-dioxolane, vinylene carbonate, propylene carbonate, ethylene carbonate, diethyl carbonate, ethyl methyl carbonate, propylene sulfite and methyl propionate.
7. The electrolyte according to claim 4, characterized in that The electrolyte includes one or more of LiPF6, LiBF4, LiBOB, LiClO4, LiCF3SO3, LiODFB, LiN(SO2CF3)2, LiN(SO2F)2, LiTFSI, LiFSI, LiHFDF, NaTFSI, KTFSI and cyclic imide salts.
8. Use of the electrolyte according to any one of claims 4 to 7 in a secondary battery.
9. A secondary battery, characterized in that: The electrolyte comprising the electrolyte according to any one of claims 4 to 7.
10. The secondary battery according to claim 9, characterized in that: The positive electrode material, the negative electrode material or the electrolyte of the secondary battery includes lithium element.
Citation Information
Patent Citations
Electrolyte for inhibiting growth of lithium dendrites and lithium-containing battery thereof
CN112216866A
Ionic liquid as well as preparation method and application thereof
CN115286522A
High-voltage electrolyte additive adaptive to lithium cobalt oxide positive electrode material and high-voltage electrolyte
CN116190787A
Additive for electrolyte solution, electrolyte solution, and secondary battery
CN116231071A
Electrolyte slurry for preparing reduced graphene through liquid flow continuous electrochemical reduction of graphene oxide
CN116288413A